Development of Sistem Informasi Pendataan Warga (Sitawar) for the Realization of Integrated Population Data at RT Level With RW - effendi, diana; Noviansyah, Berri (JIPI (Jurnal Ilmiah Penelitian dan Pembelajaran Informatika), 2017)
Citizen data collection by the majority RT still using manual way, the way it can be said not effective in terms of time of workmanship or quality of information produced.With the existence of SITAWAR can help update citizen data more effectively residing in area especially RT level.However, from the results of previous research, there are SITAWAR problems that have been built, can only be accessed by one RT only (stand alone) in one Rukun Warga area, SITAWAR has not been connected to RW level, so if the chairman of the RW is required to report demographic data that exist in the neighborhood to the village level, still done by call each existing RT in the environment or waiting for reports from each RTchairman.Looking at the issues already described, the existing SITAWAR built is developed using the concept of web application, where all RTs in one RW area are connected to the database. This research was conducted using Development Research. While the method of system development using prototype with system design tool using Object Oriented Approach and built using PHP language (Hypertext Preprocessor). With the development of SITAWAR can produce more qualified population information.